A CORRELATIONAL STUDY OF OUTDOOR EXPERIENCE QUALITY AND BEHAVIORAL INTENTIONS IN A NATURE-BASED ACCOMMODATION SETTING - Poppy Arnold Kadir (Universitas Pendidikan Ganesha, 2025)
Nature-based accommodations are increasingly attracting visitors who seek restorative outdoor experiences, positioning outdoor experiential quality as a key component of hospitality value creation. Understanding how these experiences relate to visitor behavioural tendencies is essential for strengthening loyalty within outdoor-oriented tourism settings. This study aims to examine the correlation between Outdoor Experience Quality and Behavioral Intentions in a nature-based accommodation environment. A quantitative correlational design was employed using a cross-sectional survey distributed to 200 guests who had utilized the outdoor facilities of a garden-based accommodation. The variables were measured using Likert-scale items that were subsequently transformed into three ordinal categories: good, moderate, and poor. Spearman’s Rank Correlation was used to analyse the relationship between the two variables due to their ordinal nature. Data analysis included descriptive distribution, instrument testing, and non-parametric correlation analysis. The results show that sensory, emotional, and environmental dimensions of outdoor experience were rated predominantly in the good category, indicating strong visitor appreciation of outdoor elements. Behavioral Intentions also showed high proportions of positive evaluations, particularly in word-of-mouth intention. The Spearman correlation test revealed a strong and statistically significant relationship between Outdoor Experience Quality and Behavioral Intentions (ρ = 0.536, p < 0.001). These findings confirm that favourable outdoor experiences are closely associated with stronger revisit intention, recommendation behaviour, and loyalty tendencies. This study concludes that outdoor experiential quality serves as an important correlate of behavioural intentions in nature-based accommodation settings.